Efektivitas Strategi Predict Observe Explain dan Explore terhadap Respons dan Hasil Belajar Siswa pada Materi Sistem Pernapasan di MTs Mambaul Abror Kota Mataram - Risa Umami; Fadila Soraya Zaenudin (Yayasan Tajuk Indonesia, 2024)
Abstract. Predict-Observe-Explain (POE) and Explore strategies are two constructivism-based learning approaches that have been proven effective in increasing student engagement that can encourage students to predict a phenomenon, make observations, and then explain the results of observations. This study aims to determine the effect of Predict Observe Explain and Explore-based learning strategies on student responses and learning outcomes in class VIII MTs Mambaul Abror Turida. Using Predict Observe Explain and Explore learning strategies to improve student learning outcomes in the aspects of predicting, observing, making temporary assumptions (hypotheses), exploring, making conclusions, explaining and communicating them. This research is a quantitative study, the type of research used is Quasi Experiment Design. The population in this study were students of MTs Mambaul Abror Turida. The research sample was taken using a random sampling technique, so that members of the population who participated in the sample had an equal opportunity to become members of the sample. The samples of this study were taken from 2 classes, namely class VIII A and class VIII B. The research design used Pretest Posttest Control Group Design. The research instrument was in the form of a learning outcome test in the form of an essay test and a questionnaire. Analysis of research data using statistical tests, namely the T-test using SPSS. The results of the study indicate that there is an influence of the Predict Observe Explain and Explore learning strategies on student responses and learning outcomes, which can be seen from the results of the t-test, namely the calculated T value of 2.923 and the T table value of 2.023 so that the calculated T 2.923> T table 2.023, it can be concluded that H0 is rejected and Ha is accepted.